2014
DOI: 10.1007/s10482-014-0263-8
|View full text |Cite
|
Sign up to set email alerts
|

Paenibacillus yonginensis sp. nov., a potential plant growth promoting bacterium isolated from humus soil of Yongin forest

Abstract: Strain DCY84 T , a Gram-stain positive, rodshaped, aerobic, spore-forming bacterium, motile by means of peritrichous flagella, was isolated from humus soil from Yongin forest in Gyeonggi province, South Korea. Strain DCY84 T shared the highest sequence similarity with Paenibacillus barengoltzii KACC 15270 T (96.86 %), followed by Paenibacillus timonensis KACC 11491 T (96.49 %) and Paenibacillus phoenicis NBRC 106274 T (95.77 %). Strain DCY84 T was found to able to grow best in TSA at temperature 30°C, at pH 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…For the finishing step, 500 g dried Zeolite powder was added, the mixture was sprayed with 200 ml sprayed binder solution and then it was dried. The ability to promote plant growth by P. yonginensis DCY84 T , a strain recently reported by Sukweenadhi et al (2014) was evaluated; it also can be obtained from the Korean Collection for Type Cultures (as KCTC 33428 T ) and the Japan Collection of Microorganisms (as JCM 19885 T ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the finishing step, 500 g dried Zeolite powder was added, the mixture was sprayed with 200 ml sprayed binder solution and then it was dried. The ability to promote plant growth by P. yonginensis DCY84 T , a strain recently reported by Sukweenadhi et al (2014) was evaluated; it also can be obtained from the Korean Collection for Type Cultures (as KCTC 33428 T ) and the Japan Collection of Microorganisms (as JCM 19885 T ).…”
Section: Methodsmentioning
confidence: 99%
“…Growth attributes, nutrient content and yield enhancement of rice crops by using PGPB strains as bacterial inoculants have been reported as well as of potato, sugar beet, radish and sweet potato (Manivannan, 2011;Singh et al, 2011;Farzana et al, 2009). P. yonginensis DCY84 T showed promising plant growth promoting bacteria in vitro (Sukweenadhi et al, 2014) and showed induced systemic resistance against saline stress in planta using Arabidopsis model (Sukweenadhi et al, 2015). Silicon can alleviates the effects of other abiotic stresses including salt stress, drought stress, radiation damage, nutrient imbalance, high temperatures and freezing (Ma, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…After germination, the plants were replanted separately and grown for 2 weeks in a growth chamber at 22 • C with a 16-h light photoperiod. M. yunnanensis PGPB7, P. barengoltzii PGPB8 which was designated as novel species P. yonginensis DCY84 T by Sukweenadhi et al (2014), and P. polymyxa KACC 10485 T (as positive control) were selected to inoculate A. thaliana plants. Each bacteria strain was grown on TSB media at 30 • C to late log phase.…”
Section: Bacteria Inoculation With Arabidopsis Thalianamentioning
confidence: 99%
“…Based on the screening tests, Micrococcus yunnanensis PGPB7 and Paenibacillus barengoltzii PGPB8 was selected as PGPB candidates and tested on A. thaliana. However, based on the results, our focus in this report was P. barengoltzii PGPB8 which was previously reported as a novel species, P. yonginensis DCY84 T (Sukweenadhi et al 2014). Until now, with the exception of P. polymyxa, very few reports have examined plant growth promoting activity in the Paenibacillus genera.…”
Section: Introductionmentioning
confidence: 99%
“…Many microorganisms from ginseng microfl ora have been previously explored for ginsenoside bioconversion (Kim et al 2005), plant growth-promoting activity (Singh et al 2015a, Sukweenadhi et al 2014, antimicrobial, and antagonistic activity (Farh Mel et al 2015). In the present study, a bacterial strain, W. oryzae DC6, isolated from the rhizospheric soil of mountain ginseng, has been demonstrated for the synthesis of silver nanoparticles without using any toxic chemicals, solvents, or reagents.…”
Section: Introductionmentioning
confidence: 99%